Effects of Tongue Force Training on Orolingual Motor Cortical Representation - Guggenmos, David J. (2009)
Previous research has demonstrated that training rats in a skilled reaching condition will induce task-related changes in the caudal forelimb area of motor cortex. The purpose of the present study was to determine whether task-specific changes can be induced within the orofacial area of the motor cortex in rats. Specifically, we compared changes of the orofacial motor cortical representation in lick-trained rats to age-matched controls. For one month, six water-restricted Sprague-Dawley rats were trained to lick an isometric force-sensing disc at increasing forces for water reinforcement. The rats were trained daily for six minutes starting with forces of 1g, and increasing over the course of the month to 10, 15, 20, 25 and finally 30 g. One to three days following the last training session, the animals were subjected to a neurophysiological motor mapping procedure in which motor representations corresponding to the orofacial and adjacent areas were defined using intracortical microstimulation (ICMS) techniques. We found no statistical difference in the topographical representation of the control (mean = 2.03 mm(2)) vs. trained (1.87 mm(2)) rats. This result indicates that force training alone is insufficient to drive changes in the size of the cortical representation. We also recorded the minimum current threshold required to elicit a motor response at each site of microstimulation. We found that the lick-trained rats had a significantly lower average minimum threshold (29.1 ± 1.0 μA) for evoking movements related to the task compared to control rats (34.6 ± 1.1 μA). These results indicate that while tongue force training alone does not produce lasting changes in the size of the orofacial cortical motor representation, tongue force training decreases the current thresholds necessary for eliciting an ICMS-evoked motor response.